TINGKATKAN EFISIENSI PRODUKSI DALAM INDUSTRI MENENGAH GARMEN MELALUI PENERAPAN OPERATION PROCESS CHART (OPC) - Daonil; Sabilah, Ade Irpan (LPPM-ITEBA, 2024)
In a rapidly evolving industrial era, operational efficiency and effectiveness have become key for companies to compete in the global market. This study focuses on enhancing production efficiency in the medium-sized garment industry through the implementation of process flow mapping and Value Stream Mapping (VSM). The research identifies wastage in the production process within the production division at CV. S.G and offers solutions to optimize the workflow. The results indicate that employee training and workflow reorganization can significantly increase productivity. Implementing proposed changes in the workflow activities resulted in a 30.77% decrease in total processing time, demonstrating increased efficiency and productivity. This study provides evidence that by understanding and optimizing the production flow process, medium-sized garment industries can enhance their competitiveness in the global market.